2020
DOI: 10.1128/jvi.01219-19
|View full text |Cite
|
Sign up to set email alerts
|

X4-Tropic Latent HIV-1 Is Enriched in Peripheral Follicular Helper T Cells and Is Correlated with Disease Progression

Abstract: Follicular helper T (TFH) cells have been shown to support productive human immunodeficiency virus type 1 (HIV-1) replication and to serve as a key component of the latent viral reservoir. However, the viral characteristics of this latent reservoir and the clinical relevance of this reservoir remain unclear. In this study, we assessed the tropic composition of latent viruses from peripheral TFH (pTFH), non-TFH memory, and naive CD4+ T cells from individuals with HIV-1 infections on suppressive combined antiret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Some studies observed that the frequency of cTfh cells were high in HIV-1 infected individuals ( 52 , 53 ), which was consistent with our findings ( Figure 1D ). cTfh cells are highly permissive to HIV-1 ( 54 , 55 ), where viral replication or antigen stimulation may drive the proliferation and accumulation of cTfh cells. Cytokine storm in AHI, such as elevated IL-6 and IFN-γ during HIV/SIV infection, could be potential mechanisms for the expansion of cTfh cells ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies observed that the frequency of cTfh cells were high in HIV-1 infected individuals ( 52 , 53 ), which was consistent with our findings ( Figure 1D ). cTfh cells are highly permissive to HIV-1 ( 54 , 55 ), where viral replication or antigen stimulation may drive the proliferation and accumulation of cTfh cells. Cytokine storm in AHI, such as elevated IL-6 and IFN-γ during HIV/SIV infection, could be potential mechanisms for the expansion of cTfh cells ( 56 , 57 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that peripheral follicular T helper cells are more susceptible to HIV-1 infection and are responsible for the persistence of the HIV-1 reservoir in HIV-1-infected individuals receiving cART ( 34 37 ). Therefore, using PD-1 and CXCR5 to characterize the pTFH cells in CD98 high CD4 + T cells or CD98 low CD4 + T cells, we found that the expression of CXCR5 and the proportion of pTFH cells were significantly higher in CD98 high CD4 + T cells than those in CD98 low CD4 + T cells from PBMCs of HIV-1-infected individuals receiving cART ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The env gene was ampli ed by two rounds of nested PCR. The sequences of primers are F:5'-GAGAAAGAGCAGAAGACAGTGGCAATGAGAG-3', R:5'-CTTGTAAGTCATTGGTCTTAAAGGTACCTGAGGTCTG-3' [13]. After obtaining the gene sequencing product, the data sets were subsequently evaluated with the coreceptor tropism prediction algorithm Geno2pheno (https://coreceptor.geno2pheno.org), which predicts HIV-1 coreceptor usage based on a database [14].…”
Section: The Prediction Of Viral Tropismmentioning
confidence: 99%